Androgen-Regulated Cardiac Metabolism in Aging Men - Barrientos, Genaro; Llanos, Paola; Basualto-Alarcón, Carla; Estrada, Manuel (Frontiers in Endocrinology, 2020)
The incidence of cardiovascular mortality is higher in men than in age-matched premenopausal women. Gender differences are linked to circulating sex-related steroid hormone levels and their cardio-specific actions, which are critical factors involved in prevalence and features of age-associated cardiovascular disease. In women, estrogens have been shown as cardioprotective agents, but in men the main sex steroid hormone is testosterone. The effects of testosterone as metabolic regulator and cardioprotective agent in aging men are poorly understood. With advancing age, testosterone levels gradually decline in men, which are accompanied by changes in body composition including increases in fat mass and decreases in lean body mass, dyslipidemia, insulin resistance and adjustment in glucose metabolism. Aging is associated with decline in metabolism characterized by modifications in cardiac function, excitation contraction coupling, and lower efficacy to generate energy. Testosterone deficiency as found in elderly men rapidly become epidemic conditions associated with prominent cardiometabolic disorders. Therefore, it should be considered that in older men with low testosterone levels they will have symptoms of androgen deficiency presenting an unfavorable metabolic profile and increased cardiovascular risk. Moreover, recent reports establish that testosterone replacement improves cardiomyocyte bioenergetics, increases glucose metabolism and reduces insulin resistance in elderly men. Thus, testosterone-related metabolic signaling and gene expression may represent an important therapeutic target for preventing or treating age- and gender-related cardiometabolic diseases. Here, we will discuss the impact of current evidence showing that cardiac metabolism regulated by androgens in aging men.